Tube-Based DBD Plasma Treatment for Improving the Performance of the Slippery Coating Layers on Medical Catheters - Wen, Chun-Mao; Lin, Che-Hsin (IEEE transactions on plasma science, 2021)
This work develops a tube-based dielectric barrier discharge (DBD) plasma treatment for improving the performance of the slippery coating layers on medical catheters. The raw materials of the polymer catheters usually exhibit hydrophobic surface property and need a hydrophilic slippery coating layer for reducing the friction during catheter insertion. However, the high friction force may cause an uncomfortable feeling or even the infective or thrombosis injuries on the epithelium. This study develops an atmospheric tube-based DBD plasma for treating the surface of the plastic catheter for enhancing the coating performance of the slippery layer coating on medical catheters. The tube-based DBD plasma system is a semiclose and co-axial concentric circles system composed of a glass tube as the DBD layer and the inner supporting hook for catheter production as the center electrode for DBD discharges. The treatment for the inner and outer catheter tube can be achieved simultaneously with a small carrier flow rate of 30-100 sccm. Results show that the contact angles of these catheter tubes are significantly reduced after plasma treatment and the hydrophilicity of the treated surface maintains 57% for more than 30 min after the treatments. The catheters with different plasma treatments are coated with the commercial slippery layer and tested the kinetic friction under the ASTM D1894 standard. The kinetic friction test indicates that the catheters with plasma treatment exhibit lower kinetic friction force, indicating that lower friction during catheter medical insertion operations. The experimental results have shown that the medical catheter treated by the developed tube-based DBD plasma can be effectively modified and facilitated in the subsequent coating process.